(8x+9y)(8x+9y)-(8x-9y)(8x-9y)=

Simple and best practice solution for (8x+9y)(8x+9y)-(8x-9y)(8x-9y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+9y)(8x+9y)-(8x-9y)(8x-9y)= equation:


Simplifying
(8x + 9y)(8x + 9y) + -1(8x + -9y)(8x + -9y) = 0

Multiply (8x + 9y) * (8x + 9y)
(8x * (8x + 9y) + 9y * (8x + 9y)) + -1(8x + -9y)(8x + -9y) = 0
((8x * 8x + 9y * 8x) + 9y * (8x + 9y)) + -1(8x + -9y)(8x + -9y) = 0

Reorder the terms:
((72xy + 64x2) + 9y * (8x + 9y)) + -1(8x + -9y)(8x + -9y) = 0
((72xy + 64x2) + 9y * (8x + 9y)) + -1(8x + -9y)(8x + -9y) = 0
(72xy + 64x2 + (8x * 9y + 9y * 9y)) + -1(8x + -9y)(8x + -9y) = 0
(72xy + 64x2 + (72xy + 81y2)) + -1(8x + -9y)(8x + -9y) = 0

Reorder the terms:
(72xy + 72xy + 64x2 + 81y2) + -1(8x + -9y)(8x + -9y) = 0

Combine like terms: 72xy + 72xy = 144xy
(144xy + 64x2 + 81y2) + -1(8x + -9y)(8x + -9y) = 0

Multiply (8x + -9y) * (8x + -9y)
144xy + 64x2 + 81y2 + -1(8x * (8x + -9y) + -9y * (8x + -9y)) = 0
144xy + 64x2 + 81y2 + -1((8x * 8x + -9y * 8x) + -9y * (8x + -9y)) = 0

Reorder the terms:
144xy + 64x2 + 81y2 + -1((-72xy + 64x2) + -9y * (8x + -9y)) = 0
144xy + 64x2 + 81y2 + -1((-72xy + 64x2) + -9y * (8x + -9y)) = 0
144xy + 64x2 + 81y2 + -1(-72xy + 64x2 + (8x * -9y + -9y * -9y)) = 0
144xy + 64x2 + 81y2 + -1(-72xy + 64x2 + (-72xy + 81y2)) = 0

Reorder the terms:
144xy + 64x2 + 81y2 + -1(-72xy + -72xy + 64x2 + 81y2) = 0

Combine like terms: -72xy + -72xy = -144xy
144xy + 64x2 + 81y2 + -1(-144xy + 64x2 + 81y2) = 0
144xy + 64x2 + 81y2 + (-144xy * -1 + 64x2 * -1 + 81y2 * -1) = 0
144xy + 64x2 + 81y2 + (144xy + -64x2 + -81y2) = 0

Reorder the terms:
144xy + 144xy + 64x2 + -64x2 + 81y2 + -81y2 = 0

Combine like terms: 144xy + 144xy = 288xy
288xy + 64x2 + -64x2 + 81y2 + -81y2 = 0

Combine like terms: 64x2 + -64x2 = 0
288xy + 0 + 81y2 + -81y2 = 0
288xy + 81y2 + -81y2 = 0

Combine like terms: 81y2 + -81y2 = 0
288xy + 0 = 0
288xy = 0

Solving
288xy = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '288'.
xy = 0

Simplifying
xy = 0

The solution to this equation could not be determined.

See similar equations:

| 5/6=n/42 | | 7.5x-5.7y+8.8=0 | | -8-5x=-17 | | 7y-6y+2=-9 | | 3/4M=46.50 | | 10b-2=2 | | 3/5+3 | | (3xy+2)(5xy-3)= | | 6.28/7.07 | | 4c-12=-3 | | (7x^2y-2xy-5)+(-5x^2y+5xy-10)= | | 7.07/6.28 | | 11-7*3=x | | 3/5(3)+3 | | 12b-2(b-1)=6-4b | | 5x^2-2x= | | 5/x-8 | | 4x^2+4x+1=25 | | -7*0-9y=63 | | (6-y^9)(6+y^9)= | | -7+4y+4y^2=0 | | w/7=28 | | 4a-8*(a-2)=0 | | 5(2q-1)=-5+5+10q | | 0=16t^2+10t+50 | | -t^2+12t-32=0 | | (a+5)(a+5)(a-2)=0 | | (u^2)-9u+14=0 | | 3x^3+29x^2-11x+4=0 | | (v^2)+7v+6=0 | | 7x+2(x-30)=30-(x+3) | | 9x^3+x^2-9x-1=0 |

Equations solver categories